Assessment of Inpatient Medical Record Form Design at Afifa Clinic - Risti, Amalia Wahyu; Cholifah, Cholifah; Nisak, Umi Khoirun (Indonesian Journal of Cultural and Community Development, 2024)
General background of this research focuses on the use of medical record forms in inpatient clinics, particularly at the Afifa Prambon Clinic. Specific background indicates that the forms currently used may not meet expected standards, both in terms of physical, anatomical, and content aspects. Knowledge gap lies in the lack of comprehensive analysis of the compliance of these forms with Huffman's theory. The aim of this study is to analyze the design of medical record forms at the Afifa Clinic based on physical, anatomical, and content aspects. Results of the research show that the physical aspect of the form is inadequate, such as the use of paper material that easily tears, and the anatomical aspect also does not meet standards, including the absence of form numbers and filling instructions. The novelty of this study lies in identifying the elements that need improvement in the form design and providing recommendations for enhancements. The implication of this research emphasizes the importance of improving form design to enhance the quality of medical record filling, which in turn can contribute to better healthcare services in the clinic. Highlight: Role of Music: National songs serve as powerful tools for fostering patriotism among students. Teacher Involvement: Teachers play a crucial role in integrating national songs into the curriculum. Cognitive Connection: Singing national songs enhances students' emotional and cognitive ties to their country. Keyword: Nationalism, Education, National Songs, Character Development, Patriotism